Characteristics of low-level temperature inversions over the Arctic Ocean during the CHINARE 2018 campaign in summer. (15th May 2021) - Zhang, Lei; Li, Jian; Ding, Minghu; Guo, Jianping; Bian, Lingen; Sun, Qizhen; Yang, Qinghua; Dou, Tingfeng; Zhang, Wenqian; Tian, Biao; Lu, Canggui; Zhang, Dongqi
Abstract: Across the Arctic Ocean, the semi-permanent sea-ice layer insulates the atmosphere from the Arctic Ocean, thereby influencing the lower boundary conditions of the atmosphere in this region. The presence of a temperature inversion predominantly characterizes the Arctic lower troposphere throughout the year. The 9th Chinese National Arctic Research Expedition took place in the Pacific Sectors of the Arctic Ocean from July to September 2018, gathering high-resolution radiosonde data to provide a detailed structure of the low-level temperature inversion (LLI) over the summer months. Statistical analyses showed that LLIs occurred most frequently below 500m and were generally weaker and shallower than those occurring during the winter months. Low-level inversions are influenced by both local meteorology and large scale synoptic conditions. The continual presence of low-level clouds or fog tends to lift the inversion layer at the local scale, transferring it from a surface-based inversion (SBI) to an elevated inversion (EI). By contrast, SBIs were found to dominate over regions of melting sea-ice. Regimes, where the cloud top penetrated the inversion base were more frequently observed than cloud capped by inversion regimes. Inversions tended to be deeper, stronger, and with a lower base during cloud top penetrating inversion base regimes. At the synoptical scale, the intense poleward intrusions of warm air brought moist air to the top of low-level inversions, creating a robust thermal stratification between layers and promoting extensive and frequency occurrences of low cloud/fog. Moreover, the polar high contributed to establishing a multilayer inversion structure at relatively high altitudes by subsidence. These findings contribute to an improving understanding of low-level vertical temperature structures and their influence on a rapidly warming Arctic. Graphical abstract: Image 1 Highlights: The LLIs over the Arctic Ocean are present in more than 90% of profiles with a relatively weak, shallow, and low-elevated characteristic. The presence of SBIs is more controlled by the melting ice/snow surface. The low clouds (or fog) contribute to the transition from the SBIs to EIs by cloud-top radiative cooling. The subsidence and warm air advection take turns to modulate the LLI properties, depending on the synoptic-scale circulation.